2020
DOI: 10.1186/s12876-020-01257-4
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band imaging and high-definition white-light endoscopy in patients with serrated lesions not fulfilling criteria for serrated polyposis syndrome: a randomized controlled trial with tandem colonoscopy

Abstract: Background: It is unknown whether narrow-band imaging (NBI) could be more effective than high-definition white-light endoscopy (HD-WLE) in detecting serrated lesions in patients with prior serrated lesions > 5 mm not completely fulfilling serrated polyposis syndrome (SPS) criteria. Methods: We conducted a randomized, cross-over trial in consecutive patients with prior detection of at least one serrated polyp ≥10 mm or ≥ 3 serrated polyps larger than 5 mm, both proximal to the sigmoid colon. Five experienced en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…55 A prospective tandem RCT showed that NBI and WLI yielded a similar detection rate of HPs and SSLs (HP: 18 vs. 19, SSL: 6 vs. 5, not significant) among patients diagnosed with serrated polyposis syndrome (SPS), 56 while another prospective tandem RCT similarly showed no differences in the SSLDR (NBI 47.4% vs. WLI 51.9%, OR 0.84, 95% CI 0.37-1.91) among patients without SPS. 57 Although favorable outcomes for NBI in the detection of proximal SLs were reported, the difference was not significant (NBI 204 vs. WLI 158; P = 0.085). 58 Therefore, the current evidence suggests that NBI may be used as a supplemental modality to improve the detection of SSLs, but WLI seems to be the standard approach for the detection of SLs.…”
Section: Detection Of Sessile Serrated Lesions (Ssls)mentioning
confidence: 84%
“…55 A prospective tandem RCT showed that NBI and WLI yielded a similar detection rate of HPs and SSLs (HP: 18 vs. 19, SSL: 6 vs. 5, not significant) among patients diagnosed with serrated polyposis syndrome (SPS), 56 while another prospective tandem RCT similarly showed no differences in the SSLDR (NBI 47.4% vs. WLI 51.9%, OR 0.84, 95% CI 0.37-1.91) among patients without SPS. 57 Although favorable outcomes for NBI in the detection of proximal SLs were reported, the difference was not significant (NBI 204 vs. WLI 158; P = 0.085). 58 Therefore, the current evidence suggests that NBI may be used as a supplemental modality to improve the detection of SSLs, but WLI seems to be the standard approach for the detection of SLs.…”
Section: Detection Of Sessile Serrated Lesions (Ssls)mentioning
confidence: 84%
“… 29 Additionally, a randomized controlled trial with tandem colonoscopy in patients with previous SSLs also reported no benefit of NBI over HD‐WL. 30 In a multicenter study with 138 patients, NBI has also failed to improve detection of remnant SSL tissue after EMR of serrated lesions. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Another multicenter study similarly found no significant improvement in SSLDR using NBI compared to HD‐WL endoscopy in patients with sessile serrated polyposis syndrome 29 . Additionally, a randomized controlled trial with tandem colonoscopy in patients with previous SSLs also reported no benefit of NBI over HD‐WL 30 . In a multicenter study with 138 patients, NBI has also failed to improve detection of remnant SSL tissue after EMR of serrated lesions 31 …”
Section: Discussionmentioning
confidence: 99%
“…Más recientemente, 1 ECA evaluó el rol del NBI en la detección de lesiones serradas. Riu Pons et al (40) en un estudio de colonoscopias tándem realizadas el mismo día por el mismo endoscopista, evaluaron 41 pacientes, en 21 se realizó la retirada del colonoscopio primero con NBI y luego con luz blanca de HD, y en los otros 20 se realizó la retirada primero con luz blanca de HD y luego con NBI. No hubo diferencias en la TD LS con NBI versus luz blanca de HD: 47,4% versus 51,9% (OR 0,84, IC de 95%: 0,37-1,91).…”
Section: Cromoendoscopiaunclassified